Adult paroxysmal cold hemoglobinuria following mRNA COVID‐19 vaccination. Issue 3 (15th June 2022) - Misawa, Kyohei; Yasuda, Hajime; Koyama, Daisuke; Inano, Tadaaki; Inoguchi, Akemi; Shirasu, Chinami; Takano, Hina; Iwao, Noriaki; Ando, Miki; Koike, Michiaki
Abstract: Paroxysmal cold hemoglobinuria (PCH) is an extremely rare subtype of autoimmune hemolytic anemia (AIHA) in adults. PCH is caused by the biphasic Donath–Landsteiner (DL) antibody which fixes complement to red blood cells at low temperatures and dissociates at warmer temperatures, leading to complement‐mediated intravascular hemolysis. Autoimmune hematological disorders including AIHA and immune thrombocytopenia have been reported to develop following the mRNA COVID‐19 vaccination. However, PCH developing subsequent to mRNA vaccination has never been reported. We report a 59‐year‐old male who developed PCH approximately a month after his second mRNA COVID‐19 vaccination.